2010
DOI: 10.1553/s19
|View full text |Cite
|
Sign up to set email alerts
|

The global economic crisis and international migration: An uncertain outlook

Abstract: This article investigates the impact of the global economic crisis on international migration. Empirical evidence is scarce and mainly captures short-term consequences. The study covers (1) international migration theory, (2) the impact of past financial crises on international migration, and (3) published expert opinions, studies and discussions. The impact varies by reason for migration and by migrants' employment status. Labour migration is affected most, in particular migration of low-skilled persons. Poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 4 publications
1
26
0
4
Order By: Relevance
“…This article also aims to show that the presence of immigrants, particularly if they reside in the country long enough to integrate successfully, can be beneficial for the formation of positive attitudes towards those perceived as outsiders. This would dispute current frameworks aiming to encourage return migration, proposed as the best way of managing migration during the economic crisis (Beets and Willekens, ), by suggesting that they do not improve the relations between members of host societies and communities of newcomers.…”
Section: Introductionmentioning
confidence: 81%
“…This article also aims to show that the presence of immigrants, particularly if they reside in the country long enough to integrate successfully, can be beneficial for the formation of positive attitudes towards those perceived as outsiders. This would dispute current frameworks aiming to encourage return migration, proposed as the best way of managing migration during the economic crisis (Beets and Willekens, ), by suggesting that they do not improve the relations between members of host societies and communities of newcomers.…”
Section: Introductionmentioning
confidence: 81%
“…1 on the aggregate effect of recession on public health and mortality, see the recent studies by Stuckler et al (2009), Fallagas et al (2009), and Simms (2009. For a review of the effects of economic recession on migration, see Beets and willekens (2009); for an overview of the recent evidence on that subject, see Castles and miller (2010).…”
Section: Appendixmentioning
confidence: 99%
“…Numerous studies have demonstrated that return migrant businesses are prone to failure (Petroziello and Robert 2010; Spitzer and Piper 2014). Moreover, remittances are most often used (and needed) for quotidian household expenses rather than invested in income-generating activities (Beets and Willekens 2009;Naudé, Siegel, and Marchand 2015). For example, McCormick and Wahba's (2004) study in Egypt found that about half of migrants returning to rural areas and 42% resettling in urban ones invested in familial housing, an additional 10% invested in some economic projects, while fully one-third returned home with no savings whatsoever.…”
Section: An Overview Of Return Migrant Entrepreneurshipmentioning
confidence: 99%